(untitled) (The Pakistan Development Review, 1995)
This paper assesses the role of the government in Pakistan’s agriculture sector and concludes that major reforms are needed. The government’s role is grouped into two main areas: price and trade policy, and public institutions, services, and expenditures. First, the paper assesses the impact of the price and trade policy on incentives and the functioning of input markets. Agricultural incentives have been severely distorted by policy, both through direct effects on agricultural prices and indirect effects operating through the exchange rate. Although indirect effects from the exchange rate have been corrected, some indirect effects remain because of higher protection given to industry. Subsidies on the input side have created distortions in input markets, dissipating much of the subsidy and its intended benefit to small farmers. Second, the paper looks at the role of public institutions. These have proliferated into almost every area of agriculture, with very little benefit to the sector. The most notable failure has been in the area of research and extension. Public enterprises have crowded out the private sector in marketing and distribution, and the rationale for government presence in these areas is not clear. Hidden expenditure also has taken place through underpricing of water and electricity, making the continued provision of these inputs financially unsustainable. The paper concludes that the role of government in agriculture has had little beneficial impact for most farmers and, therefore, major reforms are needed in policy and institutions to help sectoral growth.